Correlation between the stability of tRNA tertiary structure and the catalytic efficiency of a tRNA‐modifying enzyme, archaeal tRNA‐guanine transglycosylase. (10th December 2015) - Nomura, Yuichiro; Ohno, Satoshi; Nishikawa, Kazuya; Yokogawa, Takashi
Abstract : In many archaeal tRNAs, archaeosine is found at position 15. During archaeosine biosynthesis, archaeal tRNA‐guanine transglycosylase (ArcTGT) first replaces the guanine base at position 15 with 7‐cyano‐7‐deazaguanine (preQ0 ). In this study, we investigated whether modified nucleosides in tRNA substrates would affect ArcTGT incorporation of preQ0 . We prepared a series of hypomodified tRNAs S er ( GGA ) from Escherichia coli strains lacking each tRNA‐modifying enzyme. Measurement of ArcTGT kinetic parameters with the various tRNAs S er ( GGA ) as substrates showed that the K m decreased due to the lack of modified nucleosides. The tRNAs S er ( GGA ) melting profiles resulted in experimental evidence showing that each modified nucleoside in tRNA S er ( GGA ) enhanced tRNA stability. Furthermore, the ArcTGT K m strongly correlated with the melting temperature ( T m ), suggesting that the unstable tRNA containing fewer modified nucleosides served as a better ArcTGT substrate. These results show that preQ0 incorporation into tRNA by ArcTGT takes place early in the archaeal tRNA modification process. Abstract : During archaeosine biosynthesis, ArcTGT first replaces the guanine base at position 15 with preQ0 . We found the ArcTGT K m strongly correlated with the Tm, suggesting that the unstable tRNA containing fewer modified nucleosides served as a better ArcTGT substrate. This result shows that preQ0 incorporation into tRNA by ArcTGT takes place early in the archaeal tRNA modification process.